ICONIS Book Two - (Editor), Roko Patria Jati; (Editor), Zakiyuddin; (Editor), Noor Malihah (ATTARBIYAH, 2018)
The theme of this conference is "Being Muslim in a Disrupted Millenial Age". The conference was motivated by the real challenges of the millenial generation and era. Indonesia is predicted to get demographic bonus in 2020-2045. According to the calculations of the National Family Planning Board (BKKBN) RI, in the decade, as many as 70 percent of Indonesian citizens are in the productive age, which is between 15 to 64 years. Only 30 percent are unproductive, for instance under 14 years and over 65 years old. Of course, demographic bonuses have an impact on the increasing number of young people, or more specifically, millennial generation.According to Neil Howe and William Strauss in the book Millennials Rising: The Next Great Generation (2000), millennial generation are those born between 1982 and 20 years later. This means that this year, they are between 15 to 35 years old. Neil and William call the millennial as the generation that determines the future. In Indonesian context, the millennial lifestyle has had a profound influence on various aspects of personal and public life; social, cultural, economic, political and even religious. The most noticeable aspect is the increasing role of social media, which is mainly driven by the millennial generation. The role of social media, for example, has far-reaching impacts on the creative economy, with the increasing variety of digital entrepreneurship-based professions utilizing online sites, youtube, instagram, twitter and facebook. While in politics, social media becomes the personal space of branding and attention seekers that characterize millennials. Interestingly, in many parts of the world, research on millennial generation has grown considerably. In addition to the above books, some of the more popular ones were the Boston Consulting Group (BCG) and University of Berkeley research in 2011 about the millennial generation of America; The Pew Research Center Review entitled Millennials: A Portrait of Generation Next (2010). Similarly the Texas-US based Center for Generational Kinetics through the intense genhq.com site is doing recent research on Millennial and Z generations.Similar research focusing on Muslim millennials is done by the Tabah Foundation of the United Arab Emirates entitled Muslim Millennial Attitudes on Religion and Religious Leadership (2016); The work of British Muslim writer Shelina Zahra Janmohamed Generation M: Young Muslims Changing the World (2016) is also interesting. In Indonesia, research and publications on millennial generations begin, but it is still difficult to find specific references to Muslim millennials. In fact, Indonesia is a country with the largest Muslim population in the world. According to the latest data of the Cetral Intelligence Agency, the number of Indonesian Muslims reaches a range of 225 million, far beyond Muslim countries such as Iran, Turkey, Egypt, and countries in the Arabian Peninsula. The proportion of Indonesian Muslims is also very significant, namely 87.2% of the total population of Indonesia. Given that fact, Muslim millennial of Indonesia has a very strategic position in the future. Millennial Muslims in this country can lift the image of Indonesian Islam to become a world reference in realizing a peaceful and harmonious society. Actually, the image has been recognized world widely. Two decades ago, various international media praised Indonesian Islam as an ideal portrait of Muslim society. Newsweek in 1996 labeled Islam Indonesia as "Islam with a smiling face". Newsweek is so fascinated with the style of religious people in Indonesia, calling it: everyone was kind; everyone was moderate; everyone respected humanistic values and a harmonious life. Interestingly, six years ago, precisely in 2011, Indonesianist Martin van Bruinessen reviewed the label in his paper with a question: What happened to the smiling face of Indonesian Islam? Martin seemed restless with the Indonesian Islamic movement, which was originally identical with the vision of nationality and humanity, into a movement that tends to be more political and partisan.This is where Muslim millennial Indonesia can take on the role. Today, around us, the narrative of hatred seems so real. It is laid out clearly through utterances, arguments, and comments on the mass lines crammed with verbal and visual violence. With such great potential, Indonesian Muslim youth are given a choice: To let the hate narrative expand its space, or to present a counter-narrative, through viralization of virtues as the part of millennial-style. This is the significance of organizing this annual conference.